EFFECT OF SUMMER AND WINTER AIR TEMPERATURE AND HUMIDITY ON PRODUCTIVE PARAMETERS OF BROILER CHICKENS RAISED IN THE CITY OF LIMA - Tolentino M., Carlos (2008)
This study was carried out to evaluate the influence of environmental temperature and humidity on productive performance of Cobb-Vantress 500 broiler chickens reared for 45 days under an open broiler house during the winter and summer seasons (2004). The trial comprised 720 1-day-old chickens (360 chickens per season using 5 repetitions of 34 males and 38 females each). Body weight, body weight gain, feed consumption, feed conversion index, mortality, body size uniformity, and productive efficiency index were evaluated. Weekly body weight and body weight gain were statistically different between birds reared in winter and summer (p<0.05). The higher temperature during summer affected feed consumption, body weight and productive efficiency index but did not affect feed conversion index. The rearing of broiler chickens, both males and females, during the summer season as compared to winter season resulted in 200 and 100 g less per bird of body weight respectively.